Bananas of Samoa: A catalogue of banana diversity seen on the island of Upolu - Sachter-Smith, Gabriel L.; Sardos, Julie (2021)
This is a catalogue of the banana diversity seen on the island of Upolu (Samoa) during the banana expedition that took place from July, 22nd 2019 to August, 2nd 2019. It was organized by the Alliance of Bioversity International and CIAT, the Ministry of Agriculture and Fisheries of Samoa (MAF) and the Pacific Community. The expedition was funded by the Crop Trust with support of the CGIAR CRP on Roots, Tubers and Bananas.